Serum Levels of (25) 0H Vitamin-D and Hyperparathyroidism in Healthy Postmenopausal Women - Taciser Kaya; Özgür Ulutaş; Aydan Çelebiler Çavuşoğlu; Dilek Aslanca; Altınay Göksel Karatepe; Rezzan Günaydın; Baysal Karaca (Archives of Rheumatology, 2007)
Objective: 25-hydroxyvitamin D hypovitaminosis and low intake of calcium are believed to be the main reasons of secondary hyperparathyroidism in healthy postmenopausal women as well as in the elderly. In this study 25-hydroxyvitamin D deficiency and its effects on serum parathyroid hormone levels were investigated in postmenopausal women. Patients and Methods: Forty-one postmenopausal women were included into the study. Serum calcium, phosphor, creatinine, alkaline phosphatase, parathyroid hormone, 25-hydroxyvitamin D levels, calcium and creatinine levels in 24 hour urine were measured, the calcium/creatinine ratio was calculated in all subjects. All cases were divided into two groups as having normal or high parathyroid hormone levels (respectively group 1 and 2). Age, body mass index, serum levels of calcium and 25-hydroxyvitamin D were compared between groups. Furthermore, the relationship between these parameters was investigated. Results: Hyperparathyroidism was determined in 23 patients (%56.1). Serum 25-hydroxyvitamin D level showed a statistically significant difference between group 1 and 2 (p=0.030). Threshold value of 25-hydroxyvitamin D level leading to elevation in parathyroid hormone level was determined as 18.6 nmol/l. There was inverse relationship between the serum parathyroid hormone and the 25-hydroxyvitamin D levels (r=-0.357, p= 0.022). Conclusion: Secondary hyperparathyroidism due to 25-hydroxyvitamin D deficiency was detected in more than half of our cases. Thus, from this point of view we believe that it is essential to follow up not only senile but postmenopausal women as well. (Rheumatism 2007; 22: 20-3)